„YOU DO IT QUIETLY, YOU HELP AND THAT'S IT.” THE EXPERIENCE OF VOLUNTEERING THROUGH A CASE EXAMPLE - Nelli Ujhelyi (Különleges Bánásmód, 2022)
The largest population movement in the history of Europe since the Second World War has been the migration process of recent years, which also appeared in Hungary in 2015. The significant demographic movement has resulted in important social reactions and has developed different narratives in the civil and also in the power fields. In Hungary, the refugee issue has become a decisive topic of political discourse since 2015, and the party coalition was among the first in Europe to represent the security policy. As a result, the refugees appeared as a source of danger, so the government has rejected them. In spite of this, the grassroots volunteer groups were organized in the civil sphere, who helped the refugee masses passing through Hungary in 2015. This paper analyses a very brief but very intense manifestation of Hungarian civil society involvement as a social response to current conflicts. We will look at how the 2015 migration wave grassroots crisis management took place in Debrecen. This cultural anthropological research is based on online and offline participatory observations and semi-structured interviews and informal conversations with volunteers who helped refugees in Debrecen. This study focuses on the motivations, attitudes, social responsibility of volunteers and their voluntary activity embedded in broader socio-political conditions. The first part of the article shows the formation and operational peculiarities of solidarity philanthropic organization with refugees in Debrecen. Then follows the individual aspects of volunteering. Finally, it will be discussed the socio-political context of the civil voluntary movement, the political interpretations of refugee assistance, and its impact on volunteering. With outlining a segment of the contemporary volunteer phenomenon we can get closer to provide a framework for understanding the possibilities of the recent civil sphere.